Hello! what I like to do is multiply by 10s and subtract the difference, so one thing you could do is 10x256-(3x256)! your final answer will be 1792, hope this helped! ;)
Try this option:
if x+y=-9 is I (one)
and x+2y=-25 is II (two), then
if II-I, then (x+2y)-(x+y)=-25+9 ⇔ y=-16.
Answer:
Step-by-step explanation:
2^0 is less than or equal to 1!, because 1<= 1
if 2^n <= (n+1)!, we wish to show that 2^(n+1) <= (n+2)!, since
(n+2)! = (n+1)! * (n+2), and (n+1)!>= 2^n, then we want to prove that n+2<=2, which is always true for n>=0
I believe x is equal to 23
Answer:
y = 6
Step-by-step explanation:
-4 + 3y = 14
+4 +4
3y = 18
---- ----
3 3
y = 6